탄산염 혹은 황화물 풍부 조건의 하수 처리 과정을 모사한 환경에서 산화아연 (ZnO) 나노입자의 구조 변환 연구 - 이서연; Seoyeon Lee; 한준호; Junho Han; 노희명; Hee-Myong Ro (환경분석과 독성보건, 2021)
Development of nanotechnology has led to the extensive application of metal-oxide nanoparticles (NPs) in industry, and it cause toxicity and a risk to ecosystems and human health through unidentified pathways. Zinc oxide (ZnO) is one of the most versatile NPs, which causes severe direct and indirect toxicity upon transformation by environmental fluctuations. In this study, the transformation of ZnO NPs was examined in artificial sewage, wherein the sewage treatment process was simulated using either carbonate or sulfide, under oxic and anoxic conditions. Dynamic light scattering, transmission electron microscopy, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) were employed to identify the morphology and structure of the NPs. The results indicate that a decreasing in pH and ionic strength causes the aggregation of ZnO NPs, and the carbonate-rich condition leads to the growth of a spherical crystal into a rectangle form, without changing the crystal structure. XRD and XPS analysis revealed that ZnO NPs transform into the smaller ZnS NPs, sphalerite, under sulfide-rich and anoxic conditions. This implies that sewage treatment would cause the transformation of ZnO NPs into ZnS NPs, which have higher colloidal stability and dissolution rate; therefore, the transformation of NPs should be carefully examined and assessed for a better understanding and safe application. KCI Citation Count: 0